The impact of complex facial surgery provided on a short-term surgical mission. Issue 12 (December 2021) - Jenkinson, A.O.; Fell, M.; Eshete, M.; Patel, V.; Demissie, Y.; Abate, F.; McGurk, M.
Abstract: The long-term consequences of performing facial surgery on patients living in rural Ethiopia are largely unknown. A review of 36 patients who had been treated on a short-term surgical mission (STSM) in the previous 2 years was conducted to evaluate the outcomes of the surgical interventions performed. There was a significant reduction in social isolation following a surgical intervention. Improvements in postoperative self-reported changes were found for facial appearance, facial function, and quality of life. Positive outcomes can be achieved when surgical treatment is performed on a STSM.